(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics and MRI findings of patients with lumbar disc herniation undergoing surgical treatment at Viet Duc University Hospital in 2023. Research methods: A retrospective cross-sectional study was conducted on 113 patients with lumbar disc herniation who underwent surgery in 2023. Demographic data, clinical features, and MRI findings were analyzed using Spengler, Lee, Pfirrmann, and MSU classifications. Results: The mean age was 48.2 years, with the 40-59 age group accounting for 58.4%. Males predominated (male/female ratio = 1.35/1). Radicular pain was present in all patients, with a mean VAS score of 7.6 ± 1.35. Sensory deficits were observed in 86.7%, motor weakness in 35.4%, and sphincter dysfunction in 0.9%. The duration of symptoms was most commonly 1 month to under 6 months (54.0%). On MRI, the most frequently affected levels were L4-L5 (52.2%) and L5-S1 (44.2%). According to MSU classification, zone AB accounted for 55.8% and grade 2 for 61.9%. Spengler classification showed predominance of true herniation (59.3%), followed by contained (22.1%) and sequestrated (18.6%) types. Disc migration was observed in 60.2%, most commonly grade 3 (36.3%), with a predominance of downward migration. Pfirrmann grading showed mainly grade III (48.7%) and IV (36.3%) degeneration. Conclusion: Patients undergoing surgery for lumbar disc herniation were predominantly of working age and typically presented with radicular pain. MRI findings showed predominance at L4-L5 and L5-S1 levels, with a high rate of true herniation, significant migration, and moderate-to-severe disc degeneration. These findings are valuable for surgical planning and clinical decision-making.